(untitled) - Scheller, William (New York, 2008)
Answering the difficult questions that today's adventurous travelers ask-where's the best place for a beach holiday in March? What are my options if June is the only time I can take a holiday? I'm getting married in November, where would be the perfect place for a honeymoon?-this is the perfect book for anyone planning a vacation or a longer adventure. Find out about the best time to go to each destination, the best places to see, and the best things to do. Whatever you want to do, you can-and in any month of the year.
Keywords: Hoa Kỳ; Lịch sử